Correction: Decision-Making, Pro-variance Biases and Mood-Related Traits - Wanjun Lin; Raymond J. Dolan (Computational Psychiatry)
This article details a correction to: Lin, W., & Dolan, R. J. (2024). Decision-Making, Pro-variance Biases and Mood-Related Traits. Computational Psychiatry, 8(1), 142–158. https://doi.org/10.5334/cpsy.114.